Impact of the COVID-19 pandemic on acute surgical patients' discharge summaries – Experience of Wales worst-hit COVID-19 hospital. Issue 3 (June 2021) - Ooi, Rucira; Stimson, Imogen Bambrough; Williams, Gethin
Background: The emergence of the COVID-19 pandemic has placed increased demands on the NHS workforce, especially in medical and intensive care units. The subsequent redistribution of surgical house officers to accommodate this in a single-centre NHS hospital has possibly negatively impacted on the effective discharge notification of acute surgical patients. Methods: Discharge summaries of all patients directly discharged from a Surgical Assessment Unit were collected on the day of discharge and analysed to identify the date of completion and staff grade of the responsible clinician. Data collection was carried out before the initiation of lockdown measures and continued for a further three weeks during the peak of the COVID-19 pandemic with an interventional period in between. A poster was created and displayed in areas where discharge software could be accessed. Results: In the initial audit, 36.2% of the 246 patients had delayed discharge summaries with an average of 7 days to complete. On re-evaluation, 45.3% of the 223 patients had delayed discharge summaries, taking an average of 12 days to complete. A survey conducted post-re-audit identified that the most common reason for delayed discharge summaries was due to time constraints associated with the increased workload. Conclusion: The reallocation of surgical staff in response to the COVID-19 pandemic has affected communication between primary and secondary care, with a rise in delayed discharge letters of acute surgical patients. Given the potential repercussions of these delays, healthcare systems should be aware of this consequence of the pandemic, especially in preparation for any resurgences.